Correction: Mid-twenty-first century warm season climate change in the Central United States. Part I: regional and global model predictions - Christina M. Patricola-DiRosario; Kerry H. Cook (Climate Dynamics, 2026)

Correction: Northern African climate at the end of the twenty-first century: an integrated application of regional and global climate models - Christina M. Patricola-DiRosario; Kerry H. Cook (Climate Dynamics, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Role of mid-level circulation and moisture accumulation in generating Lake Victoria’s extreme storms - Edward K. Vizy; Kerry H. Cook; Patrick C. Andrews (Climate Dynamics, 2026)

Escalating heat and humidity in the Congo Basin region: projections and implications for human health and labor - Kerry H. Cook; Edward K. Vizy; Patrick C. Andrews (Climate Dynamics, 2026)

Seasonality of rainfall in the Lake Victoria Basin is controlled by the large-scale circulation - Kerry H. Cook; Patrick C. Andrews; Edward K. Vizy (Climate Dynamics, 2025)

Cloud-top brightness temperature inconsistent indicator of extreme surface rainfall in western and central equatorial Africa - Patrick C. Andrews; Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Understanding extreme rainfall in the Sahel of Southwestern Mali - Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2024)

Greenhouse gas-induced modification of intense storms over the west African sahel through thermodynamic and dynamic processes - Siyu Zhao; Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2024)

Understanding the regionality and diurnal cycles of precipitation in the Lake Victoria Basin during Boreal fall - Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2024)

Mesoscale convective systems in the Congo Basin: seasonality, regionality, and diurnal cycles - Patrick C. Andrews; Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2024)

How shrinkage of Lake Chad affects the local climate - Siyu Zhao; Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2023)

Hydrodynamics of regional and seasonal variations in Congo Basin precipitation - Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2022)

Distribution of extreme rainfall events and their environmental controls in the West African Sahel and Soudan - Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2022)

Greenhouse-gas induced warming amplification over the Arabian Peninsula with implications for Ethiopian rainfall - Kerry H. Cook; Edward K. Vizy; Yang Liu; Weiran Liu (Climate Dynamics, 2021)

Influence of Walker circulations on East African rainfall - Siyu Zhao; Kerry H. Cook (Climate Dynamics, 2021)

Delayed retreat of the summer monsoon over the Indochina Peninsula linked to surface warming trends - Yang Liu; Kerry H. Cook; Edward K. Vizy (International Journal of Climatology, 2021)
The Indochina Peninsula (ICP) is dominated by a tropical monsoon climate, and changes of the prevailing winds here have a marked impact on moisture and aerosol transport. September to early October is within the monsoon retreat period that is preceded by a change in the zonal wind from westerly to easterly. Here, we show the long‐term change of the monsoon retreat date and its related climate factors. Climatologically, the zonal wind is primarily controlled by the meridional land–sea temperature gradient through the geostrophic balance. A simple physical model suggests that a 1 K increase in this gradient is associated with a zonal wind speed change of 2.17 m·s −1 , and this estimate is consistent with reanalyses. Over the most recent 40 years there has been a positive trend of 0.107 K·decade −1 in the gradient, and linear regression shows that the average rate of delay of the summer monsoon retreat date over the ICP associated with trend in land–sea contrast is 23.5 day·K −1 . The mixing ratio gradient also makes a contribution to the monsoon retreat but its significance is lower than the land–sea temperature contrast. The ICP is located in a transitional zone bounded by three sub‐regions of Asia‐Pacific monsoon system; the delayed ICP monsoon retreat is most consistent with changes of the East Asian‐Western North Pacific monsoon.

Opposite spatial variability of climate change‐induced surface temperature trends due to soil and atmospheric moisture in tropical/subtropical dry and wet land regions - Jaya Khanna; Kerry H. Cook; Edward K. Vizy (International Journal of Climatology, 2020)
Regional responses to surface warming are strongly influenced by the availability of surface or atmospheric moisture. For example, differences in evapotranspiration, atmospheric temperature lapse rate and heat capacity due to the availability of water over oceans and its lack over land contribute to an observed land/ocean warming ratio that is greater than one. This study shows that mechanisms related to the distributions of soil or atmospheric moisture could result in variations in regional climate change over land in the tropics and subtropics. Using atmospheric reanalyses and observations for the satellite era (1979–2016) within ±30° latitude, the analysis shows that dry regions such as northern and southern Africa and south‐central Australia have a significant negative regional spatial correlation between time‐averaged soil moisture/evapotranspiration and surface temperature trends. In contrast, wet tropical regions such as Amazonia and the Congo Basin display a significant positive spatial correlation between these quantities. Spatial correlations suggest that a regional amplification of surface temperature trends in wet regions could be associated with a robust positive longwave radiative effect of high clouds which co‐occur with wet soils. This positive relationship is strongest during austral summer, dominated by the summer seasons in the Amazon and Congo basins. These differences in regional sensitivity to greenhouse gas warming can be consequential for regional climate change assessment, for both tropical forests, which could already be operating at their high temperature limit, and also for dry desert regions, which are already marginal for supporting life.

Seasonal asymmetry of equatorial East African rainfall projections: understanding differences between the response of the long rains and the short rains to increased greenhouse gases - Kerry H. Cook; Rory G. J. Fitzpatrick; Weiran Liu; Edward K. Vizy (Climate Dynamics, 2020)

Influence of Indian Ocean SST regionality on the East African short rains - Weiran Liu; Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2020)

Interannual variability of East African rainfall: role of seasonal transitions of the low-level cross-equatorial flow - Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2020)

Examining multidecadal trends in the surface heat balance over the tropical and subtropical oceans in atmospheric reanalyses - Kerry H. Cook; Edward K. Vizy (International Journal of Climatology, 2020)
Trends in the components of the annual‐mean surface heat balance for 1979–2018 over the tropical and subtropical oceans are examined in multiple atmospheric reanalyses to understand how they are changing with current sea surface temperature (SST) trends. Confidence in the reanalysis values is evaluated through statistical significance, agreement among datasets, and physical analysis. While the climatology of the net surface heat flux is similar in the three reanalyses examined (ERAI, JRA‐55, and NCEP2), net heat flux trends agree only in the two second‐generation reanalyses. Trends in the 10‐m winds, which are assimilated in JRA‐55 and ERAI but not in NCEP2, are largely responsible for the disagreement. To first order, trends in the latent heat flux explain trends in the net surface heat flux over the tropical oceans. Trends in sensible heat are smaller, and trends in the net radiative components are relevant only regionally. The latent heat flux is decomposed into thermally, dynamically, and hydrologically driven components. Trends in the thermal component of the latent heat flux simply dampen SST trends through the Clausius–Clapeyron relationship. Dynamically driven trends are associated with an intensification of the tropical easterly trade winds, primarily of the equator and with greater enhancement in the Southern Hemisphere. They are generally supported by hydrologically driven trends, which are similar in magnitude to the wind‐driven trends.

Role of the West African westerly jet in the seasonal and diurnal cycles of precipitation over West Africa - Weiran Liu; Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2020)

Congo Basin drying associated with poleward shifts of the African thermal lows - Kerry H. Cook; Yang Liu; Edward K. Vizy (Climate Dynamics, 2020)

Observed relationship between the Turkana low-level jet and boreal summer convection - Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2019)

Changes in intense rainfall events and dry periods across Africa in the twenty-first century - Fan Han; Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2019)

Contemporary Climate Change of the African Monsoon Systems - Kerry H. Cook; Edward K. Vizy (Current Climate Change Reports, 2019)

Understanding the summertime diurnal cycle of precipitation over sub-Saharan West Africa: regions with daytime rainfall peaks in the absence of significant topographic features - Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2019)

The role of mesoscale convective systems in the diurnal cycle of rainfall and its seasonality over sub-Saharan Northern Africa - Weiran Liu; Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2019)

Land–atmosphere–ocean interactions in the southeastern Atlantic: interannual variability - Xiaoming Sun; Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2019)

Decadal change of the south Atlantic ocean Angola–Benguela frontal zone since 1980 - Edward K. Vizy; Kerry H. Cook; Xiaoming Sun (Climate Dynamics, 2018)

Multidecadal-scale adjustment of the ocean mixed layer heat budget in the tropics: examining ocean reanalyses - Kerry H. Cook; Edward K. Vizy; Xiaoming Sun (Climate Dynamics, 2018)

Mesoscale convective systems and nocturnal rainfall over the West African Sahel: role of the Inter-tropical front - Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2018)

The Congo Basin Walker circulation: dynamics and connections to precipitation - Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2016)

Understanding long-term (1982–2013) multi-decadal change in the equatorial and subtropical South Atlantic climate - Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2016)

Projected changes in Malawi’s growing season - Edward K. Vizy; Kerry H. Cook; James Chimphamba; Brent McCusker (Climate Dynamics, 2015)

The relationship between African easterly waves and daily rainfall over West Africa: observations and regional climate simulations - Julien Crétat; Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2015)

Impact of cold air surges on rainfall variability in the Sahel and wet African tropics: a multi-scale analysis - Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2014)

Identifying hot spots of security vulnerability associated with climate change in Africa - Joshua W. Busby; Kerry H. Cook; Edward K. Vizy; Todd G. Smith; Mesfin Bekalo (Climatic Change, 2014)

How well are daily intense rainfall events captured by current climate models over Africa? - Julien Crétat; Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2014)

Capturing the Atlantic cold tongue and coastal upwelling in an intermediate-level ocean model coupled to a regional climate model - Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2014)

Mid-twenty-first century warm season climate change in the Central United States. Part I: regional and global model predictions - Christina M. Patricola-DiRosario; Kerry H. Cook (Climate Dynamics, 2013)

Impact of climate change on mid-twenty-first century growing seasons in Africa - Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2012)

The WAMME regional model intercomparison study - Leonard M. Druyan; Jinming Feng; Kerry H. Cook; Yongkang Xue; Matthew Fulakeza; Samson M. Hagos; Abdourahamane Konaré; Wilfran Moufouma-Okia; David P. Rowell; Edward K. Vizy; Seidou Sanda Ibrah (Climate Dynamics, 2010)

Northern African climate at the end of the twenty-first century: an integrated application of regional and global climate models - Christina M. Patricola-DiRosario; Kerry H. Cook (Climate Dynamics, 2010)

A Modeling System for Studying Climate Controls on Mountain Glaciers with Application to the Patagonian Icefields - Kerry H. Cook; Xiaosong Yang; Corinne M. Carter; Brian N. Belcher (Climatic Change, 2003)